Phenotypic and molecular characterization of released and elite sweetpotato varieties in Ghana compared with virus-tested putative ramets - Amankwaah, Victor Acheampong (2012)
A Thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirements for the Degree of Master of Science in Agronomy(Plant Breeding), August-2012